Pengaruh Aspek Psikologis Terhadap Proses Persalinan Dan Pengaruhnya Terhadap Bayi - Rizky Aprilia (Barongko: Jurnal Ilmu Kesehatan, 2026)
A mother's psychological state during pregnancy and childbirth significantly influences the smoothness of labor and the condition of the newborn. Psychological factors such as anxiety, stress, and fear can affect uterine contractions, labor duration, and the baby's physiological condition at birth. This study aims to analyze the influence of maternal psychological aspects on the labor process and its impact on the baby's condition. The study used an analytical design with a cross-sectional approach. The study sample consisted of 70 mothers in labor selected using a purposive sampling technique. Data were collected through anxiety questionnaires and observations of the labor process and the condition of the newborn. Data were analyzed using the chi-square test. The results showed that mothers with high levels of anxiety had a greater risk of prolonged labor and babies with lower Apgar scores. The statistical test showed p = 0.021 (p < 0.05). It was concluded that maternal psychological aspects significantly influence the labor process and the condition of the newborn.